Factors Associated With Abdominal Distension In Patients With Gastrointestinal Disorders - Dian Rizeki Finarti; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
Background : Abdominal distension is a common gastrointestinal complaint that May occur in patients with various digestive tract disorders . The condition May be associated with dietary patterns , constipation , physical activity , and psychological factors . Abdominal distension is multifactorial pathophysiology involving intestinal gas, delayed transit, visceral sensitivity , and abnormal abdominal wall responses. Objective : This study aimed to analyze factors associated with abdominal distension among patients with gastrointestinal disorders. Methods : This study used a quantitative analytical design with a cross-sectional approach . The sample consisted of 96 patients with gastrointestinal disorders selected using purposive sampling. Data were collected using structured questionnaires and observation sheets . The independent variables included dietary pattern , fiber intake , consumption of carbonated beverages , constipation , physical activity , and stress level, while the dependent variable was abdominal distension . Data were analyzed using the Chi- Square test with a significance level of 0.05. Results : The results showed that 41 respondents (42.7%) experienced abdominal distension and 55 respondents (57.3%) did not. Significant associations were found between dietary pattern (p=0.018), low fiber intake (p=0.009), carbonated beverage consumption (p=0.032), constipation (p=0.001), low physical activity (p=0.027), and high stress level (p=0.014) with abdominal distension. Conclusion : Dietary pattern , fiber intake , carbonated beverage consumption , constipation , physical activity , and stress were significant associated with abdominal distension among patients with gastrointestinal disorders.